Komposit Karbon Aktif dari Bahan Serbuk Gergaji Kayu Karet dan Nanomagnetik Fe3O4 + PVDF Sebagai Bahan Penyerap Limbah Cair Berbasis Logam Berat - Antonius Surbakti; Sukendi Sukendi; Erman Taer (Dinamika Lingkungan Indonesia, 2016)
Abstract: Research "of Activated Carbon Composite Materials from Rubber wood Sawdust and addition of Fe3O4 +PVDFNano-Magnetic for Liquid Waste Absorbent Materials based Heavy Metal". The study aims to measure the ability of activated carbon from rubber wood sawdust as an adsorbent of heavy metals such as Cu, Cd and Pb. This research was performed with colection and analizing data in the laboratory . The mixing process for carbon powder, nano-magnetic Fe3O4 and PVDF were use a ball-milling instrument for 2 hours. Samples were activated with KOH activating agent and followed by carbonization process at a temperature of 850 ° C. Results of the untreated samples for the liquid waste contain of Cu, Cd, and Pb with concentration of 15.2918 ppm, 5.5444 ppm and 84.9456 ppm, respectively. Once treated with rubber wood based activated carbon the maximum adsorption occurs in time immersion for 2 hours. The maximum adsorption concentration were as high as 7.8964 ppm (48.36%), 5.0067 ppm (9.69%) and 23.6320 ppm (72.17%) for Cu, Cd and Pb, respectively. The next absorption process were followed by combination of activated carbon and nano-magnetic Fe3O4, the result were 0.2592 ppm (98.30%), 4.5189 ppm (18.49%) and 1.1635 ppm (98.63%) for Cu, Cd and Pb. The maximum adsorption concentration after treated with a mixture of carbon powder and nano-magnetic Fe3O4 plus PVDF, for Cu was 0.2843 ppm (98.14%), Cd was 4.6650 ppm (15.86%) and Pb at 0.7574 ppm ( 99.10%). As a conclution can be found the increasing for the heavy metal absorption for every step experiments, and composite activated carbon, nano magnetic Fe3O4 and PVDF was the best asbsorption material for heavy metal ion in the liquid waste.